2006
DOI: 10.3233/jad-2006-10101
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids enhance amyloid-β uptake by macrophages of Alzheimer's disease patients

Abstract: Treatment of Alzheimer's disease (AD) is difficult due to ignorance of its pathogenesis. AD patients have defects in phagocytosis of amyloid-β (1-42) (Aβ) in vitro by the innate immune cells, monocyte/macrophages and in clearance of Aβ plaques [5]. The natural product curcuminoids enhanced brain clearance of Aβ in animal models. We, therefore, treated macrophages of six AD patients and 3 controls by curcuminoids in vitro and measured Aβ uptake using fluorescence and confocal microscopy. At baseline, the intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 22 publications
0
109
0
Order By: Relevance
“…Furthermore, antibody opsonization could increase inflammation (40). Therefore, the enhancement of A␤ phagocytosis (24) and gene transcription in macrophages using the natural substance curcuminoids may have important applications to the immunotherapy of AD. However, it is not clear whether the blood levels achieved after oral administration of curcuminoids would be therapeutic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, antibody opsonization could increase inflammation (40). Therefore, the enhancement of A␤ phagocytosis (24) and gene transcription in macrophages using the natural substance curcuminoids may have important applications to the immunotherapy of AD. However, it is not clear whether the blood levels achieved after oral administration of curcuminoids would be therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that a natural product curcuminoids enhanced phagocytosis of A␤ by macrophages from AD patients in Ϸ50% of the cases examined (24). We sought to identify the curcuminoid compound that is most transcriptionally and translationally active.…”
Section: Transcription Of Tlrs In Mononuclear Cells Of Ad Patients Anmentioning
confidence: 99%
“…In addition to its strong antioxidant ability, it has anti-inflammatory activity, reduces amyloid plaque burden, and partially restored distorted neuritis [125][126][127][128]. A current Phase II clinical trial that combines curcumin and yoga therapy aims to treat MCI (ClinicalTrials.gov identifier: NCT01811381).…”
Section: Oxidative Damage As a Therapeutic Targetmentioning
confidence: 99%
“…amyloid-毬 plaque formation [6][7][8] . Curcumin treatment modulates cellular and humoral immune responses of infected mice and leads to a significant reduction of parasite burden and liver pathology in acute murine schistosomiasis mansoni [9] .…”
Section: Introductionmentioning
confidence: 99%